Wells-Dawson type catalyst: An efficient, recoverable, and reusable solid acid catalyst for the solvent-free synthesis of benzodiazepines - Pasquale, Gustavo Antonio (2014)
Various 3-H-1,5-benzodiazepines were prepared from the solvent-free reaction of o-phenylenediamine and substituted 1,3-diphenyl-1,3-propanedione, giving good yields of benzodiazepines. The H6P2W18O62.24H2O solid heteropolyacid, which possesses a Wells-Dawson type structure was used as catalyst both in bulk and silica-supported forms (0.1, 0.2, 0.4 and 0.6 g/g, named 0.1WDSiO2, 0.2WDSiO2, 0.4WDSiO2 and 0.6WDSiO2, respectively). The structure of the synthesized heteropolyacid was confirmed using different characterization techniques (FTIR; 31P-RMN, and potentiometric titration).